2017
DOI: 10.1016/j.ecolmodel.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of different spatial and temporal strategies for reducing vertebrate pest populations

Abstract: Understanding effectiveness of control strategies of pest species is fundamental for planning efficient and cost-effective management programs. In addition to culling rates, there are many potential factors that can determine efficiency of different management strategies, including demographic processes such as immigration rates, birth dynamics, and spatial ecology. We developed a stochastic, data-based simulation model of feral swine population dynamics which accounted for social dynamics in space. We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 76 publications
(110 reference statements)
2
13
0
2
Order By: Relevance
“…For example, Pepin et al. () studied wild pig populations following pest control in the USA. They showed that prioritizing culling during the low‐birthing period generally resulted in faster population reduction than other temporal strategies, but this effect was small compared to the effects of spatial prioritization.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pepin et al. () studied wild pig populations following pest control in the USA. They showed that prioritizing culling during the low‐birthing period generally resulted in faster population reduction than other temporal strategies, but this effect was small compared to the effects of spatial prioritization.…”
Section: Discussionmentioning
confidence: 99%
“…) and fertility control (see Pepin et al. , b for theoretical evaluation). These are investments that have not yet been realized in terms of feral swine removals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous work has shown that prioritizing removals during non‐birthing periods can improve the efficiency of control (Pepin et al. , b), suggesting that further optimization of timing could be helpful. However, our results are national‐scale averages and previous work has indicated that forage availability can greatly impact feral swine population growth and establishment (Tabak et al.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the resources (funds, materials and labor) available for these measures are limited; thus, efficient strategies are needed to meet management goals. In particular, spatial culling quotas according to local densities are effective in wildlife management, including wild boar management (McMahon et al 2010, Pepin et al 2017). Therefore, reliable estimates of population abundance and trends are important for the adaptive management of wildlife (Nichols and Williams 2006).…”
Section: Introductionmentioning
confidence: 99%